2000
DOI: 10.1046/j.1365-8711.2000.03092.x
|View full text |Cite
|
Sign up to set email alerts
|

Time evolution of galactic warps in prolate haloes

Abstract: A recent observation with the Hipparcos satellite and some numerical simulations imply that the interaction between an oblate halo and a disc is inappropriate for the persistence of galactic warps. Then, we have compared the time evolution of galactic warps in a prolate halo with that in an oblate halo. The haloes were approximated as fixed potentials, while the discs were represented by N-body particles. We have found that the warping in the oblate halo continues to wind up, and finally disappears. On the oth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 28 publications
1
35
1
Order By: Relevance
“…Also, there is some evidence in recent literature in favour of prolate-shaped halos. For example, Ideta et al (2000) find that prolate halo helps sustain warps better. Figure 2 shows that the scaleheight upto 16 kpc radius remains almost unaffected by the change in halo shape and the effect of shape is prominent only beyond 20 kpc.…”
Section: Shape Of the Halomentioning
confidence: 99%
“…Also, there is some evidence in recent literature in favour of prolate-shaped halos. For example, Ideta et al (2000) find that prolate halo helps sustain warps better. Figure 2 shows that the scaleheight upto 16 kpc radius remains almost unaffected by the change in halo shape and the effect of shape is prominent only beyond 20 kpc.…”
Section: Shape Of the Halomentioning
confidence: 99%
“…This model requires a halo that is much more massive than the disc, an extremely high accretion rate (3 disc masses in 0.9 Gyr; Jiang & Binney 1999) and, in this scenario, after a sufficiently long time, the angular momentum of the Galaxy to become parallel to the direction of the falling matter causing the warp to decay. It is difficult to understand why the warps are so frequent in this scenario but this difficulty might be overcome by including a prolate halo (Ideta et al 2000), which would prolong the warp's existence. Also, it is difficult to understand how a low-density halo can retain the accreted intergalactic matter.…”
Section: Introductionmentioning
confidence: 99%
“…Cosmological simulations demonstrate that dark matter halos are inclined to be more frequently prolate than oblate (Dubinski & Carlberg 1991;Warren et al 1992). In addition, prolate halos can be supported from the standpoint of the longevity of galactic warps; Ideta et al (2000) have shown that a warped structure persists for a long time in a prolate halo, while it disappears quickly in an oblate halo.…”
mentioning
confidence: 99%